Blast Waves Cause Immune System Dysfunction and Transient Bone Marrow Failure in a Mouse Model - Bergmann-Leitner, Elke S.; Bobrov, Alexander G.; Bolton, Jessica S.; Rouse, Michael D.; Heyburn, Lanier; Pavlovic, Radmila; Garry, Brittany I.; Alamneh, Yonas; Long, Joseph; Swierczewski, Brett; Tyner, Stuart; Getnet, Derese; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Explosive devices, either conventional or improvised, are common sources of injuries during combat, civil unrest, and terror attacks, resulting in trauma from exposure to blast. A blast wave (BW), a near-instantaneous rise in pressure followed by a negative pressure, propagates through the body in milliseconds and can affect physiology for days/months after exposure. Epidemiological data show that blast-related casualties result in significantly higher susceptibility to wound infections, suggesting long-lasting immune modulatory effects from blast exposure. The mechanisms involved in BW-induced immune changes are poorly understood. We evaluated the effects of BW on the immune system using an established murine model. Animals were exposed to BWs (using an Advanced Blast Simulator), followed by longitudinally sampling for 14 days. Blood, bone marrow, and spleen were analyzed for changes in the 1) complete blood count (CBC), and 2) composition of bone marrow cells (BMC) and splenocytes, and 3) concentrations of systemic cytokines/chemokines. Our data demonstrate that BW results in transient bone marrow failure and long-term changes in the frequency and profile of progenitor cell populations. Viability progressively decreased in hematopoietic stem cells and pluripotent progenitor cells. Significant decrease of CD4+ T cells in the spleen indicates reduced functionality of adaptive immune system. Dynamic changes in the concentrations of several cytokines and chemokines such as IL-1α and IL-17 occurred potentially contributing to dysregulation of immune response after trauma. This work lays the foundation for identifying the potential mechanisms behind BW’s immunosuppressive effects to inform the recognition of this compromised status is crucial for the development of therapeutic interventions for infections to reduce recovery time of wounded patients injured by explosive devices.